2020
DOI: 10.1177/0020764020959093
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of internet addiction in healthcare professionals: Systematic review and meta-analysis

Abstract: Background: Internet addition is becoming increasingly recognised as an important mental health problem. Aim: This study examined prevalence of internet addiction in healthcare professionals. Method: Systematic literature review was undertaken of June 4, 2020 with goal to identify studies that evaluated prevalence of internet addiction or problematic internet use in medical professionals. Reported associations with other mental health symptoms were also considered. Results: Prevalence of internet addiction was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
2
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 39 publications
1
30
2
7
Order By: Relevance
“…Recent studies have shown possible association of burnout with physical, psychological and occupational consequences such as cardiovascular disorders, diabetes, depression and addictive behaviour [ 10 , 11 , 12 ]. There are limited data about the association of burnout and problematic internet use as a behavioural addiction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown possible association of burnout with physical, psychological and occupational consequences such as cardiovascular disorders, diabetes, depression and addictive behaviour [ 10 , 11 , 12 ]. There are limited data about the association of burnout and problematic internet use as a behavioural addiction.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, intrapersonal variables were statistically shown to have larger effects on IA than interpersonal variables according to a recent meta-analysis [ 9 ]. IA is mainly studied in adolescents, but it may also occur among adults and can be associated with greater mental symptom burden and fatigue [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite numerous advantages of Internet-based technologies in medical training and the healthcare system, there is still a growing body of evidence that excessive Internet use could lead to PIU among healthcare professionals and cause comorbid problems related to mental health. The prevalence rate for PIU was reported at 7.2% in the general population (Pan et al, 2020) compared with 9.7% among healthcare professionals (Buneviciene and Bunevicius, 2020) and 30.1% among medical students (Zhang et al, 2018). It is well-recognized that medical students and resident doctors are at a greater risk for mental health problems when compared with the general population (Puthran et al, 2016;Erschens et al, 2019;Zeng et al, 2019;Zhou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Az internetfüggőség gyakran szorongással, depresszióval, tiltott szerhasználattal és malnutrícióval társulhat, továbbá iskolai/munkahelyi kiégéshez vezethet [4,8,9]. Az előbb felsorolt mentális rendellenességek és internet addikció közötti okokozati kapcsolat nem teljesen tisztázott [4,8,9,10].…”
Section: Internet Addiction Sleep Disturbance Depression and Quality Of Life Among Healthcare Workersunclassified
“…Az internetfüggőség döntően fiatalkorúaknál vizsgált jelenség, de felnőtteknél is előfordul, noha az erre vonatkozó irodalmi adatok még messze nem teljesek [10].…”
Section: Internet Addiction Sleep Disturbance Depression and Quality Of Life Among Healthcare Workersunclassified